Representasi Taman Literasi Bidang Perbankan Berbasis Corporate Social Responsibility - Utari, Sri; Anawati, Sri; Demartoto, Argyo (Ilmu Informasi Perpustakaan dan Kearsipan, 2021)
The library is a place for learning resources, in the millennial era it should provide a public space for learning. Universitas Sebelas Maret, Surakarta has a Literacy Park (LP) as a public space, the result of the collaboration between UNS and BNI through Corporate Social Responsibility (CSR) of BNI-Berbagi Program. The purpose of this study aims to determine the representation of TL in the banking sector based on CSR. The research method used is an exploratory qualitative method. Collecting data by observation, interviews, Focus Group Discussion and documentation. TL representation is the fulfillment of information literacy needs, students can get the latest information in the banking sector and have a comfortable place to study, and free from rules.